MECHANISMS OF STATE REGULATION INTEGRATION OF SCIENCE IN UKRAINE - Lutsenko T.A. (Pressing Problems of Public Administration, 2015)
The article analyzes the current state of scientific and scientific-technical activities in Ukraine. The theoretical basis for the development of the state regulation of science. The conclusion for improving the institutional state regulation scientific and scientific-technological activities in Ukraine is made.